Twenty-five years of Mercator ocean reanalysis GLORYS12 at Drake Passage: Velocity assessment and total volume transport - Artana, Camila; Ferrari, Ramiro; Bricaud, Clément; Lellouche, Jean-Michel; Garric, Gilles; Sennéchael, Nathalie; Lee, Jae-Hak; Park, Young-Hyang; Provost, Christine (Advances in Space Research)
Velocities in Drake Passage from the 25-year GLORYS12 Mercator Ocean reanalysis were compared with satellite altimetry-derived surface velocities and independent in-situ velocity measurements from the DRAKE (2006–2009) and cDrake (2007–2011) experiments. GLORYS12 assimilates satellite along-track sea level anomalies and, as expected, model velocities are in rather good agreement with gridded altimetry derived velocities (r ~ 0.5, above 99% confidence level). GLORYS12 velocities also compared well with the current-meter data from the DRAKE (in the water column) and cDrake (50 m above seafloor) experiments in terms of means and standard deviations; most correlations between the reanalysis and directly measured velocity time series were significant (r ~ 0.5 for DRAKE and r ~ 0.4 for cDrake, above 99% confidence level). We used the GLORYS12 reanalysis to examine the Antarctic Circumpolar Current (ACC) total volume transport across three sections in Drake Passage. The 25 years of the ACC total volume transport has a mean of 155 ± 3 Sv and a standard deviation of 6.7 Sv. Annual mean values span over a range of 12 Sv. The spectrum of the GLORYS12 total transport time series shows energy peaks (above 95% confidence level) at the intraseasonal, semi-annual and annual periods and no significant low-frequency variations (beyond 2 years) or trend, in agreement with previous studies. This first assessment of GLORYS12 velocities in Drake Passage is very encouraging for monitoring the regional variability of the ACC. Fil: Artana, Camila. Universite de Paris VI; Francia Fil: Ferrari, Ramiro. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Centro de Investigaciones del Mar y la Atmósfera. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Centro de Investigaciones del Mar y la Atmósfera; Argentina Fil: Bricaud, Clément. No especifíca; Fil: Lellouche, Jean-Michel. No especifíca; Fil: Garric, Gilles. No especifíca; Fil: ...